Crack-healing during two-stage crystallization of biomedical lithium (di)silicate glass-ceramics - Belli, Renan; Lohbauer, Ulrich; Götz-Neunhoeffer, Friedlinde; Hurle, Katrin (Dental Materials, 2019)
Objective: The study is aimed to evaluate the two single commercially available two-step lithium-(di)silicate systems by analyzing their parent glass composition and studying the quantitative crystalline and glass phase evolution during the second stage heat-treatment. The mechanical repercussions of the crystallization firing were evaluated using strength and fracture toughness tests. Methods: XRF and ICP-OES were used to determine the oxide composition of the parent glasses in Suprinity PC (Vita Zahnfabrik) and IPS e.max CAD (Ivoclar-Vivadent). The crystalline phase of both materials was determined by quantitative XRD and the G-factor method in the partially and post-crystallization states. The oxide composition of the residual glass phase was derived by subtracting the chemistry of the crystalline phase fractions from the parent glass composition. Mechanical testing of biaxial flexural strength and fracture toughness were used to demonstrate how crack-like defects behave during crystallization. Results: The two tested lithium (di)silicate systems showed strong differences in oxide composition of the parent glass. This showed to influence the transformation of lithium metasilicate in lithium disilicate, with the former remaining in high vol.% fraction in the post-crystallization Suprinity PC. In IPS e.max CAD cristobalite precipitated at the surface during the second-heat treatment. Strength and fracture toughness tests revealed that crack in both materials, whether introduced by grinding or indentation, heal during the crystallization firing. Cristobalite seemed to have contributed to a surface strengthening effect in IPS e.max CAD. Significance: Accurate crystalline phase quantification aids in the determination of the residual glass composition in dental glass-ceramics. For both systems crystallization firing induced healing of cracks generated by CAM grinding.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Dental; Fracture toughness; Glass-ceramic; Lithium disilicate; Lithium silicate; X-ray diffraction